2021
DOI: 10.1177/0363546520982241
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Tibial Slope in Patients Undergoing Anterior Cruciate Ligament Reconstruction With Patellar Tendon Autograft: Analysis of Subsequent ACL Graft Tear or Contralateral ACL Tear

Abstract: Background: Reports on greater posterior tibial slope (PTS) and its relationship to subsequent anterior cruciate ligament (ACL) injury show conflicting results; it has not been studied much in patients after ACL reconstruction with patellar tendon autograft (PTG). Hypothesis: Patients who suffered a subsequent ACL injury would have a larger PTS than patients who did not suffer a subsequent injury after primary or revision ACL reconstruction. Study Design: Cohort study; Level of evidence, 3. Methods: Patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 26 publications
1
34
1
Order By: Relevance
“…There were also 2 studies that used the anterior tibial cortex 19 , 97 and 3 studies that used the posterior tibial cortex for their measurement techniques. 43 , 44 , 86 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were also 2 studies that used the anterior tibial cortex 19 , 97 and 3 studies that used the posterior tibial cortex for their measurement techniques. 43 , 44 , 86 …”
Section: Resultsmentioning
confidence: 99%
“… 58 , 104 Others have shown that patients with graft rupture after previous ACL reconstruction (ACLR) have greater PTS than those undergoing primary ACLR. 72 , 86 To protect reconstruction grafts from variations in PTS, some authors advocate the use of slope reducing, anterior closing-wedge high tibial osteotomy. 22 , 24 , 27 …”
mentioning
confidence: 99%
“…More recently, some authors have shown that patients with posterior tibial slope .10°had a higher rate of subsequent graft tear, leading the investigators to consider osteotomy in these cases to prevent retear. 27 All of these anatomic parameters may play a role in the pathogenesis of ACL tears; however, it should be noted that ''normal'' differences exist according to sex and ethnicity. For example, the intercondylar notch is wider in men than in women, 6,17,20,28,30 which may explain the higher prevalence of ACL injuries in women.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, some authors have shown that patients with posterior tibial slope >10° had a higher rate of subsequent graft tear, leading the investigators to consider osteotomy in these cases to prevent retear. 27…”
Section: Discussionmentioning
confidence: 99%
“…Shelborne 11 suggested that female players had relatively high frequency of knee injuries, and knee surgery took time to recover. In recent years, serious injuries in female players have also been reported.…”
Section: Introductionmentioning
confidence: 99%